Firm Characteristics and Capital Structure - Devi Anjar (Accounting and Finance Studies, 2021)
This research is aimed to determine the effect of the profitability, company size, growth and taxes on the infrastructure, utilities, and transportation sector companies’capital structure which are registered in the Bursa Efek Indonesia. The dependent variable on this research is capital structure while the independent variables on this research are profitability, company size, and growth. The data used in this research is secondary data which is taken from the company’s annual financial report. Meanwhile, the population of this research is infrastructure, utilities, and transportation sector companies which are registered in the Bursa Efek Indonesia. The sampling technique used is purposive sampling method within the final sample of 186 companies have been obtained. The analysis technique used is panel data regression analysis by using Eviews 10 program. The result shows that profitability and company size give negative effect toward capital structure. Meanwhile, growth have no effect toward capital structure.